PENGUKURAN COMPUTED TOMOGRAPHY DOSE INDEX (CTDI) PADA FANTOM KEPALA DENGAN MENGGUNAKAN CT DOSE PROFILER - Ahadiyah, Naeli Ni'matin; Setiawati, Evi; Arifin, Zaenal; Anam, Choirul (BERKALA FISIKA, 2020)
This study aims to measure computed tomography dose index (CTDI) on a head polymethyl methacrylate (PMMA) phantom using a CT dose profiler for various slice thicknesses. The slice thicknesses were 3, 5, and 10 mm. Dose measurements were performed in spiral mode for every hole within the head PMMA phantom. A CT dose profile analyzer software integrated the profile dose along 100 cm to find the CTDI100. The CTDIw was calculated as 1/3×(CTDI100,center)+2/3×(average CTDI100, perifer). Since the pitch was unity, the CTDIvol was similar to the CTDIw. The values of CTDIvol for slice thickness variations were from 45.7 mGy to 46.0 mGy. This result indicated that there is no significant different of CTDIvol measured using CT dose profiler for slice thicknesses from 3 mm up to 10 mm.Keywords: CT dose profiler, CTDI, CTDI100, CTDIw, CTDIvol, slice thickness